Students as Partners versus Students as Employees: Division of Labour between Students, Faculty, and Staff in the McMaster Student Partners Program - Suart, Celeste; Harvey, Kelsey; Zhu, Jennifer; Ali, Maham; Cassidy-Neumiller, Martha (Imagining SoTL)

(untitled) (Mount Royal University Library in partnership with University of Alberta Library, 2023)
Many post-secondary institutions have implemented students-as-partners frameworks to redefine traditional educational practices and value students as co-creators of knowledge. The aim of this study was to investigate the degree to which students are working as partners and co-creators of knowledge with faculty and staff, versus replicating traditional hierarches. Herein, we undertook a multi-methods study consisting of a secondary analysis and a survey of one cohort of the student-as-partners program at McMaster University, as well as qualitative interviews. We found that some languages practices replicated traditional hierarchies, which was reflected in the degree to which partners contributed intellectually to the work undertaken. However, we also found meaningful shifts in practices occurred over the course of working collaboratively to foster more equitable partnerships. Herein, faculty and staff bore the responsibility of sharing power with student partners, but the blurring of professional and personal boundaries complicated the ethics of partnership.